Analisis Yuridis Kewenangan Pengadilan Hubungan Industrial Dalam Penanganan Kasus Union Busting - Kleine Fitri Vimelita; Tuti Widyaningrum; Wagiman .; Januar Agung Saputera (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the legal authority of the Industrial Relations Court (PHI) in handling union cases in Indonesia and to identify the ideal regulatory concept for protecting workers’ freedom of association. Using a normative juridical research method with statutory and conceptual approaches, this research examines the disharmony between Law Number 21 of 2000 regarding Trade Unions and Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement. The results indicate a significant enforcement gap where union busting action, which are criminally sanctioned under Article 43 of Law 21/2000, are often reduced to individual civil disputes in the PHI. Furthermore, court decisions frequently prioritize formal procedures over substantive justice, failing to provide structural recovery for labor unions. This study recommends a legislative reform to include “freedom of association disputes” as a distinct category in the PHI’s absolute competence and the implementation of a reverse burden of proof to effectively safeguard constitutional rights.